Anti-Inflammatory Pathways Mediating tDCS’s Effects on Neuropathic Pain - Haipeng Zhang; Xinyan Zheng; Binn Zhang (Biology)
Neuropathic pain (NP) is a prevalent clinical condition resulting from diseases or injuries affecting the somatosensory system. Conventional analgesics often exhibit limited efficacy, leading to suboptimal therapeutic outcomes. The pathogenesis of NP is complex and involves multiple mechanisms. The existing evidence suggests that maladaptive neuronal plasticity plays a central role in NP development. Additionally, emerging research highlights the contribution of neuroinflammatory responses mediated by glial cells in the onset of NP and associated sensory hypersensitivity. Among non-invasive neuromodulation techniques, transcranial direct current stimulation (tDCS) has gained prominence as a potential treatment for NP. Numerous studies have demonstrated its analgesic effects; however, the precise regulatory mechanisms remain unclear. The current evidence indicates that tDCS may alleviate NP by enhancing glial–neuronal interactions, which suppress nociceptive signaling pathways and reduce pain sensitivity. The reciprocal modulation between tDCS-mediated anti-inflammatory actions, as evidenced by decreased levels of pro-inflammatory cytokines and increased levels of anti-inflammatory mediators, and its facilitation of adaptive neural plasticity represents a particularly compelling therapeutic axis. This review elucidates inflammatory regulation by tDCS as a fundamental mechanism for NP alleviation, while delineating important unresolved questions regarding these complex interactions.